Successful treatment of cardiac dysrhythmia associated with foot and mouth disease in a calf - Priyanka, M. (Iran J Vet Res, 2019)
BACKGROUND: Foot and mouth disease (FMD), which causes myocarditis, results in 50% sudden death in the suckling calves. Occurrence of arrhythmias associated with FMD induced myocarditis in calves is not reported hitherto. ‏‏‏The present work documents the arrhythmias associated with FMD in calf and their treatment using appropriate antiarrhythmic drugs. CASE DESCRIPTION: A three-month-old male Holstein Friesian crossbred calf naturally suffering from FMD was selected for the present study. FINDINGS/TREATMENT AND OUTCOME: Cardiac auscultation revealed grade 4 systolic murmurs and electrocardiography (ECG) showed sustained polymorphic ventricular premature complexes (PVPCs) with tachycardia on bipolar base apex lead. Apart from standard treatment, lidocaine 2% was administered at dose of 0.6 mg/kg intravenously over 15 min once a day and sinus rhythm was restored by 76 h post-treatment. Review of ECG and haematobiochemical examination revealed normal findings on 7th day of treatment. CONCLUSION: The study demonstrates the presence of sustained PVPCs with tachycardia due to FMD induced myocarditis and the successful use of lidocaine in restoring the sinus rhythm and recovery of the calf.